PENGARUH MATA KULIAH KEWIRAUSAHAAN TERHADAP MINAT BERWIRAUSAHA MAHASISWA PENDIDIKAN EKONOMI PPAPK FKIP UNTAN PONTIANAK - Erni Dahlia; Endang Purwaningsih; Sri Buwono (Universitas Tanjungpura, 2019)
AbstractThis study aim is to learn how much the influence of entrepreneurship course towards interest in entrepreneurship for economics education student in FKIP UNTAN Pontianak. The research method used is an explanatory method with a form of causality research. The object source of this research is from PPAPK Semester IV economic education students and the form of data in this study is a questionnair, guidelines and results of interviews with lecturers of entrepreneurship courses. The results of research showed that the influence of entrepreneurship courses on the interest of student entrepreneurship was 52%, which meant that the entrepreneurial course is